2022
DOI: 10.3389/fpsyg.2022.960029
|View full text |Cite
|
Sign up to set email alerts
|

The association between sleep problems and general quality of life in cancer patients and in the general population

Abstract: ObjectiveIt is well-known that patients with cancer frequently experience sleep problems, and that sleep quality is associated with general quality of life (QoL). The aims of this study were to analyze the relationship between sleep problems and other components of QoL in more detail and to investigate sex and age differences in sleep quality in cancer patients in comparison with the general population.MethodThis study comprised one general population sample (n = 4,476) and eight samples with cancer patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In accordance with the other studies, our results showed that educational levels, BMI, physical activity level, family local residency, ethnicity, current smoking status, current opioid use, and alcohol consumption are not associated with sleep quality. 35 , 49 , 50 There is no consensus regarding the association of age with sleep among patients with cancer; while some studies show an association with sleep distribution, 51 - 57 the Ratcliff’s study did not find the same association. 49 …”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the other studies, our results showed that educational levels, BMI, physical activity level, family local residency, ethnicity, current smoking status, current opioid use, and alcohol consumption are not associated with sleep quality. 35 , 49 , 50 There is no consensus regarding the association of age with sleep among patients with cancer; while some studies show an association with sleep distribution, 51 - 57 the Ratcliff’s study did not find the same association. 49 …”
Section: Discussionmentioning
confidence: 99%
“…Reimer and Flemons argue for using broad-based instruments in study cohorts to cover concepts that include physical, mental, and social function, the burden of symptoms and an overall sense of well-being [133]. Instruments with broader coverage of QoL concepts have also been recommended in the sleep literature, given that sleep and circadian factors are strongly correlated with broad concepts of daily mental and physical performance and well-being [36][37][38][39]. Our review has shown that nearly 45% of economic evaluations of sleep disorder interventions have a mix of generic and sleep-specific instruments, perhaps in recognition that neither type of instrument may be sufficiently comprehensive to cover the breadth of potential sleep-related QoL constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Instruments such as the ESS and ISI are also predominantly used as diagnostic tools and not strictly QoL instruments. Further, sleep (and circadian) factors strongly influence many aspects of daily mental and physical performance and wellbeing, thus broad QoL impacts from sleep disorders should be anticipated [36][37][38][39][40][41]. Hence, it is vital to establish an appropriately sensitive, specific, reproducible, and standardised approach to measure QoL as an outcome of treatment that can be applied widely within the economic evaluation framework.…”
Section: Key Points For Decision Makersmentioning
confidence: 99%
“…Linear regression analysis identified poor sleep quality as a primary factor for the decline in physical and mental health QoL. A recent study [29] found a significant negative correlation between sleep disturbances and all QoL domains, with psychological aspects more affected than physical health. Prior studies have linked sleep disorders with reduced QoL, depression [30], concentration difficulties [31], fatigue, and lower survival rates [12].…”
Section: Relationship Among Sleep Disorders Sleep Quality and Health-...mentioning
confidence: 91%